Klasifikasi Risiko Hipertensi Menggunakan Fuzzy Decision Tree Iterative Dichotomiser 3 (ID3) - Mochamad Rafli Andriansyah; Edy Santoso; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Hypertension is a disease where the heart and the arteries have abnormalities which is indicated by the increase of blood pressure. Hypertension can be controlled if it's handled from the early stage, however, several number of patients only earn the knowledge right after there's a complication of failures of the organs. Considering that hypertension is one of the very lethal diseases, the researchers have done researches about the classification of hypertension, one of them used Fuzzy Decision Tree with ID3 algorithm. To solve the problem about hypertension based on the available factors, the study use Fuzzy Decision Tree ID3 method to classify the risks of hypertension that have initialization stages of Fuzzy values, the calculation of Fuzzy enthropy values, and the values of information gain, as well as defuzzification to determine the result of the classification. The testing that has been carried out could result in the highest accuration value, which is 80%, derived from the testing of 30 training data dan 20 testing data, as well as the combination of the FCT and LDT value. The conclusion of the research that has been accomplished is that Fuzzy Decision Tree ID3 can solve the problems in the classification of hypertension risks quite well.